CRYSTAL CHEMISTRY OF THE ELBAITE-SCHORL SERIES - Bosi F.; Andreozzi G.B.; Federico M.; Graziani G.; Lucchesi S. (My University, 2005)
The crystal-chemistry of 13 elbaite-schorl tourmaline crystals from the Cruzeiro pegmatite (Minas Gerais, Brazil) was studied with a multi-analytical approach (SREF, EMPA, SIMS, MS). Effective cation radii at the Y and Z sites and site populations were refined by a minimization procedure. The results indicate that the crystals belong to the alkali group. Elbaite crystals are O2−-free at the W and V sites and show OH content at the O2 site (up to 0.2 apfu). Conversely, schorl crystals always show O2− at the W site. The main substitutional mechanism is the dehydroxylation type: The T site is characterized by TSi → TAl substitution. is linearly correlated with vacancy content in crystals with (OH + F) ≤ 4, whereas it is almost constant in crystals with OH at the O2 position. Along the series, is inversely correlated with YAl. The Z site is almost fully occupied by R3+ (with ZAl largely dominant) and the ZFetot ↔ ZAl substitution explains the inverse correlation of with ZAl. In the elbaite compositional range, lattice parameters are functions of , whereas in the schorl range they are essentially functions of . Along the whole elbaite-schorl series, both chemical substitutions and size increase of Y are far larger than those of Z. In spite of this, lattice parameters increase with as much as with . This is due to the role of the [ZO6] polyhedra, which extend along a and c to form the skeleton of the tourmaline structure. Therefore, any change in the size of Z leads to a change in the whole structure.
Keywords: crystal chemistry; elbaite; schorl; tourmaline